Expression of insulin-like growth factor I gene in osmoregulatory organs during seawater adaptation of the salmonid fish: possible mode of osmoregulatory action of growth hormone. - Sakamoto, T (1993)
Growth hormone has been shown to contribute to seawater adaptation of salmonid fishes. The growth influence of growth hormone is mediated largely by hepatic production of insulin-like growth factor I (IGF-I). To study the growth hormone-IGF-I axis in osmoregulation, we measured IGF-I mRNA in the liver, gill, and body kidney from rainbow trout by Northern analysis. The levels of IGF-I mRNA in all tissues increased significantly after injection of growth hormone. Transfer of trout from fresh water to 80% seawater evoked an increase in plasma growth hormone after 1 day. IGF-I mRNA was not altered significantly in the liver, but it was increased in the gill and body kidney after 1 and 8 days, respectively. These observations indicate that the IGF-I gene is expressed differently among these organs during seawater adaptation. Growth hormone may stimulate hypoosmoregulatory ability by inducing local expression of IGF-I in osmoregulatory organs, although the possibility that IGF-I expression might occur in part independently of growth hormone during seawater adaptation cannot be excluded.